Prevalence of metabolic syndrome, its continuous severity score, and correlated cardiovascular risk among postmenopausal women of a selected rural area of Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Our primary objective was to estimate the prevalence of metabolic syndrome (MetS) among postmenopausal women (PMW) and evaluate the correlation of its severity score with the risk of cardiovascular diseases (CVD). In addition, we compared the distribution of CVD risk and risk factors among PMW with or without MetS.Methods: We recruited 265 PMW of 40-70 years of age from February to December 2016 who had no CVD. The MetS was defined according to modified Adult Treatment Panel III criteria and MetS severity score was constructed using a standardized Z score. CVD risk was assessed using the lab-based Globorisk score.Results: About 35.1% of the PMW had MetS. The proportion of central obesity, generalized obesity, physical inactivity, diabetes, and hypertension were higher among those with MetS than those without. A highly significant CVD risk score difference (P